Role of subjects in natural sciences in forming scientific and research competency in future light industry production technologists - Djachenko, Ludmila (NTU "KhPI", 2018)
Modern approaches to forming scientific and research competency in students are viewed in the article; forms and methods to activate student’s scientific and research activity in natural sciences are presented as well. A significant role of natural sciences subjects in forming students’ experience in scientific and research activity is accentuated. Scientific and research work in natural sciences carries in itself a great potential for improvement of modern specialists’ professional training and forming necessary competencies in them.

В статі розглянуто сучасні підходи до формування науково-дослідницької компетентності студентської молоді, представлено форми і методи активізації науково-дослідницької діяльності студентів з природничих дисциплін. Акцентовано увагу на значущій ролі дисциплін науково-природничого напряму у формуванні досвіду науково-дослідницької діяльності. Науково-дослідницька робота з природничих дисциплін несе в собі великий потенціал, який спрямовано на удосконалення професійної підготовки сучасних фахівців та формування в них необхідних компетентностей.
Роль природничих дисциплін у формуванні науково-дослідницької компетентності майбутніх техніків-технологів легкої промисловості
Keywords: scientific and research competency; subjects in natural sciences; project; scientific and research activity; specialist’s professional training; науково-дослідницька компетентність; природничі науки; проект; науково-дослідницька робота; професійна підготовка фахівців